Modellunterstützte Beurteilung der Verkehrsqualität auf Netzabschnitten von Bundesautobahnen - Hartmann, Martin (Schriftenreihe des Instituts für Verkehrswesen, Karlsruher Institut für Technologie, 2019)
An efficient highway capacity design is becoming an increasingly important topic, thanks to recurring congestions and unreliable travel times in the German highway network. This work provides a new methodology for the analysis of oversaturated freeway facilities. A Cell Transmission Model was used as an underlying traffic flow model for modeling oversaturated freeway facilities and tailor-fitted to represent the HBS manual faithfully.